PERANCANGAN MODEL WISATA EDUKASI DI SUBAK TEBA MAJALANGU, DESA KESIMAN KERTALANGU KOTA DENPASAR - Suryaningsih, Ida Ayu Anggreni; Shintya Nita Kristiana Putri, Komang; Karina Putri, Ida Ayu (Jurnal IPTA (Industri Perjalanan Wisata); Vol 11 No 2 (2023): Jurnal IPTA (December 2023)DO - 10.24843/IPTA.2023.v11.i02.p04, 2024)
Subak Teba Majalangu is an educational tourist destination located in the village of Kesiman Kertalangu Village, Denpasar City. This place offers nature-based educational tourism activities with Balinese history and culture as its main attraction. This research aims to design an educational tourism concept for Subak Teba Majalangu. Type of This research is descriptive with a qualitative approach. Data collection was carried out through observation, interviews, and document studies. The design of the educational tourism model in the research consists of tutorial and exploration learning methods. The purpose of tutorial learning is to provide basic knowledge about various things found in Subak Teba Majalangu. Majalangu. Exploration learning aims to increase the visitors' knowledge and understanding by directly seeing the object of learning.